Developing research willpower at one South African university as a strategy to transform higher education institutions : experiences of the mentees - Israel, Kariyana; Newlin, Marongwe (Penerbit Universiti Kebangsaan Malaysia, 2021)
Universities are mandated to be institutes thriving on three pillars namely teaching and learning, research and community engagement. Higher education institutions (HEIs), however, value and prioritise these pillars differently and consequently implement them on different scales in their day-to-day operations. HEIs also engage postdoctoral research fellows to partly drive their research operations while developing these fellows to be fully-fledged independent researchers. The objective of this study was to ascertain the extent to which developing research willpower at one South African university was a strategy to transform higher education institutions based on the experiences of two fellows. A case study research design within a mixed method approach was utilised. Stratified random sampling was used to identify the 37 participants for the study. Data was gathered using questionnaires, individual face-to-face interviews, focus group discussions and document analysis. It emerged that developing research willpower in HEIs is a daunting but possible process which is masked by environmental, socio-economic and technological factors. Participants pointed out to existing constraints and possible opportunities to curtail the prevailing negative institutional research culture.